# Properties of Adjoints of Linear Maps

Recall from The Adjoint of a Linear Map page that if $V$ and $W$ are finite-dimensional nonzero inner product spaces and that $T \in \mathcal L (V, W)$ then the adjoint of $T$ is the linear map $T^* \in \mathcal L (W, V)$ defined by considering the linear function $\varphi : V \to \mathbb{F}$ defined by $\varphi(v) =

We will now look at some properties of adjoints in the following propositions.

Proposition 1: Let $V$ and $W$ be finite-dimensional nonzero inner product spaces. Let $S, T \in \mathcal L(V, W)$. Then $(S + T)^* = S^* + T^*$. |

**Proof:**We note that $ =$ by the definition of an adjoint. Furthermore, we have that:

(1)

- Thus we have that $(S + T)^* = S^* + T^*$. $\blacksquare$

Proposition 2: Let $V$ and $W$ be finite-dimensional nonzero inner product spaces. Let $T \in \mathcal L(V, W)$ and let $a \in \mathbb{F}$. Then $(aT)^* = \overline{a}T^*$. |

**Proof:**We note that $ =$ . Furthermore, we have that:

(2)

- Thus we have that $(aT)^*(w) = \overline{a}T^*(w)$. $\blacksquare$

Proposition 3: Let $V$ and $W$ be finite-dimensional nonzero inner product spaces. Let $T \in \mathcal L(V, W)$. Then $(T^*)^* = T$. |

**Proof:**We note that $ =$ . Furthermore, we have that:

(3)

- Thus we have that $(T^*)^* = T$. $\blacksquare$

Proposition 4: If $I$ is the identity operator on a finite-dimensional nonzero inner product space $V$ then $I^* = I$. |

**Proof:**We note that $*=*. So $I^*(w) = w$ and so $I^* = I$. $\blacksquare$= $

Proposition 5: Let $U$, $V$ and $W$ be finite-dimensional nonzero inner product spaces. Let $S \in \mathcal L(W, U)$ and let $T \in \mathcal (V, W)$. Then $(ST)^* = T^*S^*$. |

**Proof:**We note that $ =$ . Furthermore we have that:

(4)

- Thus we have that $(ST)^* = T^*S^*$. $\blacksquare$

## Example 1

**Let $T$ be a linear operator on the inner product space $V$. Prove that $T = T^2$ if and only if $T^* = (T^*)^2$.**

$\Rightarrow$ Suppose that $T = T^2$. Then if we take the adjoint of both sides of this equation then we get that:

(5)

Here we applied Proposition 5 to the second equality. Therefore $T^* = (T^*)^2$.

$\Leftarrow$ Suppose that $T^* = (T^*)^2$. Then if we take the adjoint of both sides of this equation then we get that:

(6)

Here we applied Proposition 3 and Proposition 5. Therefore $T = T^2$.